2021
DOI: 10.1136/bmjopen-2021-051957
|View full text |Cite
|
Sign up to set email alerts
|

Play interventions for paediatric patients in hospital: a scoping review

Abstract: ObjectivePlay is a non-invasive, safe and inexpensive intervention that can help paediatric patients and their families manage difficult aspects of being ill or hospitalised. Although play has existed in hospitals for decades, research on hospital play interventions is scarce. This review aimed to categorise and synthesise the last 20 years of research on hospital play interventions.DesignScoping review.Data sourcesPubMed, CINAHL, CENTRAL, ERIC and PsycINFO (1 January 2000– 9 September 2020).Study selection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 59 publications
0
20
0
5
Order By: Relevance
“…It is argued the scoping approach enhances rigour, thus reducing biased searches, and provides focus and boundaries for the review. The scoping review method has been used successfully for several recent healthcare literature reviews [8][9][10].…”
Section: Review Methodologymentioning
confidence: 99%
“…It is argued the scoping approach enhances rigour, thus reducing biased searches, and provides focus and boundaries for the review. The scoping review method has been used successfully for several recent healthcare literature reviews [8][9][10].…”
Section: Review Methodologymentioning
confidence: 99%
“…Há tempos o brincar tem sido reconhecido como um meio para as crianças lidarem com os desafios da doença e hospitalização. 1 Na modalidade terapêutica há evidências de seu impacto na promoção do bem-estar e redução do medo e ansiedade, por permitir a criança expressar e lidar com as dificuldades enquanto brinca com diversos brinquedos e conta com a presença de um adulto que acolhe suas manifestações e anseios. 2,3 Recente revisão de escopo identificou que nos últimos vinte anos as intervenções lúdicas têm sido utilizadas no cuidado em saúde da criança, como: forma de preparo e suporte para os procedimentos; medida não farmacológica no manejo da dor por meio da distração; suporte educacional para potencializar as habilidades e atitudes sobre a doença e o tratamento; forma de promover a adaptação nos diversos contextos, por meio da recreação e atividades voltadas para o enfrentamento da hospitalização com redução da ansiedade, estresse e melhora do humor.…”
Section: Introductionunclassified
“…Play has long been recognized as a way for children to deal with the challenges of illness and hospitalization 1 . In the therapeutic modality, there is evidence of its impact on promoting well-being and reducing fear and anxiety, as it allows the child to express and deal with difficulties while playing various games, with the presence of an adult who respects their manifestations and anxieties 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent scoping review identified that in the last twenty years play interventions have been used in child health care, as a preparation and support for procedures, a non-pharmacological measure in pain management through distraction an educational support to enhance skills and attitudes regarding the disease and treatment, and as a way to promote adaptation in different contexts, through recreation and activities aimed at coping with hospitalization with reduced anxiety, stress and improved mood 1 .…”
Section: Introductionmentioning
confidence: 99%